Management of esophageal perforation with fistula formation in an 80 year old woman with multiple co-morbidities - Almarzooq, Jalal; Alkhabbaz, Ayman; Abdulla, Nabeel (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Esophageal perforation due to foreign body ingestion may lead to serious complications. Here we present a case of an 80 year old lady with multiple co-morbidities who presented with a proximal esophageal perforation with fistula formation following ingestion of a fish bone. Due to her age and co-morbidities the decision was made to manage her conservatively by IV antibiotics, NG tube feeds and observation. Follow up after 2 months showed resolution of the perforation and fistula, without the patient needing any surgical intervention. This case highlights conservative management of esophageal perforation with complications in patients with co-morbidities where open surgery is not favoured.